A Realization of Stabilizing the Output Light Power from a Laser Diode: A Practical Approach - Chughtai, M. T. (Engineering, Technology & Applied Science Research, 2021)
Semiconductor Laser Diodes (LDs) are known for their sensitivity to variation in ambient temperature. With the rise in case temperature the threshold current of the LD increases, causing the output light power to deteriorate drastically. Therefore, it is necessary to stabilize the temperature of the diode. Various approaches could be adopted in this regard. In this paper, an active cooling approach using the temperature compensation technique has been followed and presented in the form of a full design of the circuit according to the various datasheet parameters of the LD and other components. As a result of temperature stabilization, a significant improvement in the output light power stabilization was observed and the results are presented.